2009
DOI: 10.1002/mds.22660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three clinical rating scales in Friedreich ataxia (FRDA)

Abstract: To test the validity and reliability of the scale for the assessment and rating of ataxia (SARA) in Friedreich ataxia (FRDA). SARA is limited to eight items and can be performed rapidly. Ninety-six patients with a molecular genetic diagnosis of FRDA were rated using three different clinical scales, the FRDA Rating Scale (FARS), the International Cooperative Ataxia Rating Scale (ICARS), and SARA. Despite considerable discrepancies in scale size and subscale structure, SARA total scores were significantly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 16 publications
5
100
2
4
Order By: Relevance
“…The overall range of the total sum score is broader in ICARS than in SARA (100 versus 40 points), and rating results in all SARA items seem to be loaded on a single factor, whereas Ͼ1 factor is determined in the ICARS. 24,25 Hence, the SARA only rates ataxia-related symptoms. 25 This possibly leads to a higher contribution of cerebellar volume loss on the disease severity score, especially in diseases in which ataxia is dominant.…”
Section: Discussionmentioning
confidence: 99%
“…The overall range of the total sum score is broader in ICARS than in SARA (100 versus 40 points), and rating results in all SARA items seem to be loaded on a single factor, whereas Ͼ1 factor is determined in the ICARS. 24,25 Hence, the SARA only rates ataxia-related symptoms. 25 This possibly leads to a higher contribution of cerebellar volume loss on the disease severity score, especially in diseases in which ataxia is dominant.…”
Section: Discussionmentioning
confidence: 99%
“…The three clinical groups were matched for two parameters, i.e., (1) disease severity (measured by the Scale for the Assessment and Rating of Ataxia (SARA) [14,15] administered by a neurologist not involved in the assessment of the dysarthria profile) and (2) disease duration (Table 1). One-way ANOVA revealed no significant between-group differences, neither for overall SARA-score (SARA total ; F (2, 27) = 0.238; p = 0.79) nor for disease duration (F (2, 27) = 0.371; p = 0.69).…”
Section: Participantsmentioning
confidence: 99%
“…The ICARS scale evaluates two items related to visual function: postural and stance disturbances, and oculomotor dysfunction, whereas none of the items scored by the FARS scale are related to visual function. 19 Fortuna et al 1 found positive correlations between scores obtained in the ICARS test and disease duration, and mean RNFL thickness. However, they did not find a significant correlation with contrast sensitivity as we did.…”
mentioning
confidence: 96%